Primary prevention implantable cardioverter defibrillator in cardiac resynchronization therapy recipients with advanced chronic kidney disease - Goldenberg, Ido; Kutyifa, Valentina; Zareba, Wojciech; Huang, David Tsu-Chau; Rosero, Spencer Z.; Younis, Arwa; Schuger, Claudio; Gao, Anna; McNitt, Scott; Polonsky, Bronislava; Steinberg, Jonathan S.; Goldenberg, Ilan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: The implantable cardioverter defibrillator (ICD) is effective for the prevention of sudden cardiac death (SCD) in patients with heart failure and a reduced ejection fraction (HFrEF). The benefit of the ICD in patients with advanced CKD, remains elusive. Moreover, the benefit of the ICD in patients with advanced chronic kidney disease (CKD) and HFrEF who are cardiac resynchronization therapy (CRT) recipients may be attenuated.Hypothesis: We hypothesized that patients with CKD who are CRT recipients may derive less benefit from the ICD due to the competing risk of dying prior to experiencing an arrhythmia. Methods: The study population included 1015 patients receiving CRT with defibrillator (CRT-D) device for primary prevention of SCD who were enrolled in either (Multicenter Automated Defibrillator Implantation Trial) MADIT-CRT trial or the Ranolazine in High-Risk Patients with Implanted Cardioverter Defibrillator (RAID) trial. The cohort was divided into two groups based on the stage of CKD: those with Stage 1 to 3a KD, labeled as (S1-S3a)KD. The second group included patients with Stage 3b to stage 5 kidney disease, labeled as (S3b-S5)KD. The primary endpoint was any ventricular tachycardia (VT) or ventricular fibrillation (VF) (Any VT/VF).Results: The cumulative incidence of Any VT/VF was 23.5% in patients with (S1-S3a)KD and 12.6% in those with (S3b-S5)KD (p<0.001) The incidence of Death without Any VT/VF was 6.6% in patients with (S1-S3a)KD and 21.6% in patients with (S3b-S5)KD (p<0.001). A Fine and Gray multivariate competing risk regression model showed that Patients with (S3b-S5)KD had a 43% less risk of experiencing Any VT/VF when compared to those with (S1-S3a)KD (HR=0.56, 95% CI [0.33-0.94] p=0.03. After two years of follow up, there was almost a 5-fold increased risk of Death without Any VT/VF among patients with (S3b-S5)KD when compared to those with (S1-S3a) KD (HR=4.63,], p for interaction with time=0.012).Conclusion: Due to their lower incidence of arrhythmias and higher risk of dying prior to experiencing an arrhythmia, the benefit of the ICD may be attenuated in CRT recipients with advanced CKD. Future prospective trials should evaluate whether CRT without a defibrillator may be more appropriate for these patients.